The Oxford dictionary of nursery rhymes - Opie, Iona, 1923-2017.; Opie, Peter (Oxford ; New York : Oxford University Press, 1997)
Over five hundred traditional nursery rhymes, accompanied by illustrations and detailed notes about each rhyme.
Includes indexes.
Keywords: Nursery rhymes; Children's poetry